2015
DOI: 10.4322/rca.1861
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of cover materials in preventing evaporation in drought-stressed soybeans grown in pots

Abstract: ABSTRACT:There are few studies in the specific literature on the use of cover materials to control evaporation in drought-stressed plants grown in pots under greenhouse conditions. The use of these materials is of great importance to ensure that water loss occurs only through transpiration. Thus this study aimed to investigate the efficiency of different cover materials -polyethylene, marble, polystyrene, and polyvinyl chloride (PVC) -in controlling evaporation in black and in silver pots cultivated with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…One day before the water deficiency was induced (at the end of the afternoon), all pots were saturated with water and the excess water was allowed to drain overnight. On the following morning, the pots were wrapped in polyethylene bags and the central region of the pots was covered with cotton around the stem base to prevent water loss by evaporation, as described by Ferreira et al (). The control plants were well hydrated, whereas irrigation was withheld from the water deficiency group.…”
Section: Methodsmentioning
confidence: 99%
“…One day before the water deficiency was induced (at the end of the afternoon), all pots were saturated with water and the excess water was allowed to drain overnight. On the following morning, the pots were wrapped in polyethylene bags and the central region of the pots was covered with cotton around the stem base to prevent water loss by evaporation, as described by Ferreira et al (). The control plants were well hydrated, whereas irrigation was withheld from the water deficiency group.…”
Section: Methodsmentioning
confidence: 99%
“…A study carried out by Ferreira et al (2015) would have tested the covering of vessels with varied materials considering soybean and demonstrated that the isolation is effective in causing water losses to be the result only of transpiration, which was crucial to this experiment. Therefore, the soil was isolated with aluminum foil to reduce gas exchange between the medium of interest and the rhizosphere, and irrigation was administered directly into the ground.…”
Section: Soilmentioning
confidence: 99%